Determinants of the long-run performance of initial public offerings : Evidence from the Nordic markets 1996–2016 - Oulujärvi, Juho (My University, 2022)
The aim of the thesis was to analyze the long-run performance and determinants of IPOs on the Nordic stock markets. This was done by reviewing theoretical frame works, previous empirical studies and finally analyzing the sample of Nordic IPOs. The study’s theoretical part reviewed why companies go public, IPO process, efficient market and behavior theories in order to understand companies’ decisions to go public and reasons behind the performance of the IPOs. In previous studies, it was mainly observed that IPOs underperform over the next three years. In this study, buy-and-hold abnormal returns (BHAR) and cumulative abnormal returns (CAR) have been selected as measurement methods of the long-run performance. The study sample consisted of 274 IPOs in Nordic countries during 1996–2016. Overall, Nordic IPOs underperformed -8.0 measured by BHARs and -9.7 measured by CARs during three-year measuring period. The performance of IPOs was also analyzed country basis. In Denmark, Finland and Norway IPOs underperformed compared to country-specific index and in Sweden, IPOs overperformed on the long run. The country-specific results were partially statistically significant and partially in line with the previous studies done in Nordic countries. Furthermore, the empirical work in this thesis attempted to clarify the determinants of the long-run performance of IPOs. Previous empirical studies provided many determinants which are affecting the long-run performance of IPOs. Similar studies have found that for example size, age, initial return of the IPO, exercised overallotment option, multiply underwriters, hot-issue market, venture capital backed IPO could explain long-run performance of IPOs. These determinants were chosen for the further examination in the empirical part. The empirical analysis was conducted with linear regression models. However, these findings from Nordic IPOs only partially supported the previous findings. Initial returns, age of the company and multiple underwriters were in line with most of the previous empirical findings. Whereas, size of the company, issuing during the hot-issue period, exercising overallotment option and venture capital backed IPOs did not support the previous findings.

Tämän tutkielman tavoitteena on tutkia listautumisantien pitkän aikavälin tuottoa ja siihen vaikuttavia tekijöitä pohjoismaisilla osakemarkkinoilla. Näiden selvittämiseksi tutkielmassa tarkastellaan teoreettisia viitekehyksiä, aiempia empiirisiä tutkimuksia ja analysoimalla pohjoismaisten listautumisantien pitkän aikavälin tuottoa ja siihen vaikuttavia tekijöitä. Tutkimuksen teoreettisessa osassa tarkastellaan yritysten syitä listautua, listautumisprosessia, tehokkaita markkinoita ja käyttäytymisteorioita, jotta ymmärrettäisiin yritysten motiiveja listautua pörssiin ja pitkänaikavälin suoriutumiseen vaikuttavista tekijöistä. Aiemmissa tutkimuksissa on pääosin havaittu, että listautumisannit tuottavat keskimäärin markkinoita huonommin seuraavan kolmen vuoden aikana. Tässä tutkimuksessa pitkän aikavälin suoriutumista mitataan osta-ja-pidä -menetelmällä (BHAR) ja kumulatiivisten epänormaalien tuottojen (CAR) avulla. Tutkimusotos koostui 274 listautumisannista Pohjoismaissa vuosina 1996–2016. Kaiken kaikkiaan pohjoismaiset listautumisannit alisuoriutuivat markkinaan nähden -8,0 osta-ja-pidä -menetelmällä ja -9,7 kumulatiivisella epänormaalit tuotot -menetelmällä mitattuna kolmen vuoden mittausjaksolla. Listautumisantien tuottoja analysoitiin myös maakohtaisesti. Tanskassa, Suomessa ja Norjassa listautumisannit tuottivat maakohtaista indeksiä heikommin ja Ruotsissa listautumisannit tuottivat pitkällä aikavälillä markkinaindeksi paremmin. Tulokset olivat osittain tilastollisesti merkitseviä ja osittain linjassa aiempien Pohjoismaissa tehtyjen tutkimusten kanssa. Lisäksi tämän tutkielman empiirisessä osiossa selvitettiin listautumisannin pitkän aikavälin tuottoon vaikuttavia tekijöitä. Aikaisemmat tutkimukset ovat osoittaneet, että esimerkiksi koko, ikä, listautumisannin alkuperäinen tuotto, käytetty lisäosakeoptio, pääjärjestäjien lukumäärä, kuumat markkinat ja riskipääomasijoittajien osallistuminen voivat selittää listautumisannin pitkän aikavälin tuottoja. Näitä tekijöitä analysoitiin tarkemmin lineaarisen regressiomallien avulla. Havainnot tukivat kuitenkin vain osittain aikaisempia tutkimuksia. Lyhyen aikavälin tuotto, yrityksen ikä ja pääjärjestäjien lukumäärä olivat linjassa useimpien aikaisempien empiiristen havaintojen kanssa. Sen sijaan yrityksen koko, listautuminen kuuman ajanjakson aikana, lisäosake option käyttäminen ja riskipääomasijoittajien osallistuminen eivät tukeneet aiempia havaintoja.
Keywords: IPO, long-run performance, Nordic, determinants